Challenging the Gates: Religious Freedom and Access in South Africa's Theology Faculties - Thinane, Jonas Sello (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2023)
The location, acceptance, and tolerance of religious education in public spaces have been fiercely debated since South Africa’s democratic transition in 1994. As a result, South Africa’s constitution now guarantees religious freedom in all public places, including educational institutions. The primary question is, however, how much do these public universities’ theological and religious faculties guarantee that all religious or faith traditions have equal access to their curricula? Simply put, this article examines the theological and religious education programs at universities such as the University of the Free State (UFS), North-West University (NWU), Stellenbosch University (SU), and University of Pretoria (UP) and asks whether they promote justice to the extent that they incorporate all faith traditions into their curricula. Given this, the paper posits that the majority of religious communities are not sufficiently represented in the curricula of South African public universities’ theological and religious faculties. It then advocates, as a practical measure, the establishment of the theological-religious ombudsman to guarantee that students of all faiths have equitable access to theological and religious curricula at South African public universities.